연관관계 군집 분할 방법을 이용한 아이템 필터링 시스템 - 조동주(Dong-Ju Cho); 정경용(Kyung-Yong Jung); 박양재(Yang-Jae Park) (한국콘텐츠학회 논문지, 7(6), 2007)
In electronic commerce, it is important for users to recommend the proper item among large item sets with saving time and effort. Therefore, if the recommendation system can be recommended the suitable item, we will gain a good satisfaction to the user. In this paper, we proposed the associative relation clustering split method in the collaborative filtering in order to perform the accuracy and the scalability. We produce the lift between associative items using the ratings data. and then split the node group that consists of the item to improve an efficiency of the associative relation cluster. This method differs the association about the items of groups. If the association of groups is filled, the reminding items combine. To estimate the performance, the suggested method is compared with the K-means and EM in the MovieLens data set. 전자상거래에서 많은 아이템 중에 사용자에게 적합한 아이템을 추천하기 위해서는 많은 시간과 노력이 소요된다. 그러므로 추천 시스템이 사용자들을 대신하여 적합한 아이템을 추천해줄 수 있다면 만족을 얻을 수 있다. 본 논문에서는 정확성과 확장성을 향상시키기 위해서 협력적 필터링에서 연관관계 군집 분할 방법을 제안하였다. 평가한 데이터를 사용하여 연관 아이템간의 향상도를 산출하고 연관관계 군집의 효율성을 높이기 위해서 아이템으로 구성된 노드 군집을 분할하였다. 이는 군집들 중 하나의 아이템만이 연관성을 달리하고, 나머지 아이템들은 군집의 연관성이 충족되어진다면 결합하는 방법이다. 성능을 평가하기 위해서 MovieLens 데이터 집합에서 K-means와 EM에 의한 군집과 비교 평가하였다.